PENGEMBANGAN MEDIA PEMBELAJARAN KOSAKATA BAHASA JERMAN TEMA REISEN KELAS XII SMA NEGERI 1 MENGANTI POSTER MIT 3D-POSTKARTE - Kazhimah, Rubie; Titaley, Audrey (LATERNE, 2025)
This research aimed to develop and assess the feasibility of a German vocabulary learning medium themed "Reisen" (Travel) for 12th-grade students at SMA Negeri 1 Menganti, using a medium titled "Poster with 3D Postcard". This medium was an innovative learning tool that combines visual posters, three-dimensional pockets, and vocabulary cards with corresponding images based on the Reisen theme. The research employed the Research and Development (R&D) method, applying three of the five ADDIE model stages: Analysis, Design, and Development. Data was collected through observations, interviews, and validation by media experts and subject matter experts. The validation resulted show that the developed medium received a feasibility score of 98% from the media expert and 96% from the subject expert. This indicated that the medium was considered “very valid” and appropriated for use in the learning process. The researched also shows that the "Poster with 3D Postcard" learning medium can be further developed for other German language learning themes to make vocabulary acquisition more varied.